Innovation Strategy for Civil Servant HR Development in the Digitalization Era: BPSDMD Banten Province - Defi Nuryadin; Feri Fadli Rizki; Lufki Lufki (ijd-demos, 2025)
Local governments are required to adapt to electronic systems through the Electronic-Based Government System (SPBE) policy. The Human Resources Development Agency (BPSDMD) of Banten Province faces challenges such as low digital literacy among civil servants, a conventional work culture, and limited network infrastructure. This study aims to evaluate the effectiveness of innovation strategies for civil servant human resource development in addressing these challenges, utilizing Chandler’s strategy theory and Bekkers’ digitalization framework. A descriptive qualitative approach was employed, involving interviews, observations, and document analysis. The results indicate that BPSDMD Banten Province successfully implemented blended learning and distance learning methods, while optimizing the "Banten Ceria" and "Teko Banten" Learning Management Systems (LMS). Key supporting factors included central policy support, physical facilities, and regional budget (APBD) allocations; conversely, network disruptions and participants' digital literacy gaps served as obstacles, which were mitigated through human-centric support and the simplification of application interfaces. It is concluded that digitalization innovation strategies are crucial for bureaucratic transformation; however, they require continuous post-training performance evaluation and the enrichment of interactive features to maximize employee competence in public service. Recommendations include strengthening backup internet infrastructure, recruiting additional programming experts, and expanding micro-learning content to ensure the innovation remains responsive to technological advancements. Keywords: Strategy; Innovation; Human Resource Development; Civil Servants; Digitalization